2000
DOI: 10.1159/000055909
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-Induced Tumour Cell Migration in an in vivo Chicken Model

Abstract: To investigate the relationship between hypoxia, neovascularisation and tumour cell spread, experiments on the area vasculosa of the early chick embryo under different oxygen concentrations were performed in vivo. Human glioblastoma cells (U-138MG) were inoculated onto the area vasculosa and the fertilised eggs were incubated under conditions of normoxia or hypoxia. For evaluation, we performed in vivo video-microscopy of the area vasculosa and determination of microvessel density (MVD), as well as a histologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 30 publications
(38 reference statements)
0
16
1
Order By: Relevance
“…The differences in stem potential of those cells describe the characteristics of primary and metastatic cells rather than the contribution of CD105+. Also, in contrast to other studies, we have shown that in the case of pRCC, hypoxic conditions in vitro diminish the stem-like properties of cell lines [7985]. …”
Section: Discussioncontrasting
confidence: 99%
“…The differences in stem potential of those cells describe the characteristics of primary and metastatic cells rather than the contribution of CD105+. Also, in contrast to other studies, we have shown that in the case of pRCC, hypoxic conditions in vitro diminish the stem-like properties of cell lines [7985]. …”
Section: Discussioncontrasting
confidence: 99%
“…Another transcription factor that can activate the c-Met promoter under normoxic as Previous studies suggested that hypoxia can stimulate glioma cell migration and invasion, although the responsible mechanisms have so far remained unclear. [18][19][20] In this study we analyzed 3 glioblastoma cell lines in which c-Met was inducible by hypoxia. We found that hypoxia by itself stimulated the migration of only 1 of these cell lines (U87), but enhanced the motogenic effects of SF/HGF on all 3 cell lines.…”
Section: Hypoxia Synergizes With Sf/hgf In Inducing Glioma Cell Migramentioning
confidence: 99%
“…14 Hypoxia has been found to also increase the migration of glioma cells, although the mechanisms of this stimulation have so far remained unclear. [18][19][20] We hypothesized that the induction of cMet via HIF-1 might be one such mechanism. We therefore analyzed (i) whether c-Met protein and mRNA are inducible by hypoxia in glioma cells, (ii) whether the hypoxic induction of c-Met is mediated through HIF-1a and (iii) whether hypoxia can enhance the effect of SF/HGF on glioma cell migration in vitro.…”
mentioning
confidence: 99%
“…This results in additional resistance to radiotherapy and chemotherapy (2) and further increase in angiogenesis and a more aggressive tumor potential (35). …”
Section: Introductionmentioning
confidence: 99%